Corticosteroids as “God Drugs”: Between Therapeutic Efficacy and Side Effects - Oktorra, Elsya Jaisi; Permana, Dicka Trie; Amanda, Revana Putri; Fitriyani, Fitriyani; Puspita, Reva Sri; Nurcholisa, ⁠Siti; Putri, Rd. Natasya Aurellia; Ridwan, Heri (Ahmar Metastasis Health Journal, 2025)
Corticosteroids are potent anti-inflammatory and immunosuppressive agents widely used in clinical practice due to their rapid therapeutic effects. Despite their proven efficacy, prolonged and inappropriate use is associated with a wide range of adverse effects affecting multiple organ systems. This systematic review aimed to evaluate the therapeutic benefits of corticosteroids and to summarize their reported side effects based on literature published between 2015 and 2025. A systematic search was conducted using Google Scholar, PubMed, and ScienceDirect with the keywords “corticosteroids,” “benefits,” and “side effects.” Eligible studies were full-text, open-access articles published in English or Indonesian. Eight articles met the inclusion criteria and were analyzed descriptively. The findings indicate that corticosteroids are effective in managing inflammatory conditions such as asthma, autoimmune diseases, atopic dermatitis, nephrotic syndrome, and postoperative inflammation. However, long-term use is associated with metabolic and endocrine disturbances (hyperglycemia and Cushing’s syndrome), musculoskeletal complications (osteoporosis and osteonecrosis), dermatological effects (skin atrophy and irritation), ocular disorders (increased intraocular pressure and glaucoma), and cardiovascular effects. Systemic corticosteroids pose the highest risk of adverse effects, while topical and ocular formulations predominantly cause local reactions but may still lead to serious complications with prolonged use. Children and older adults are particularly vulnerable. In conclusion, corticosteroids remain essential in clinical therapy, but their use must be rational, closely monitored, and supported by patient education to minimize long-term risks.